Voriconazole versus itraconazole for antifungal prophylaxis following allogeneic haematopoietic stem-cell transplantation - Marks, David; Pagliuca, Antonio; Kibbler, Christopher C.; Glasmacher, Axel; Heußel, Claus Peter; Kantecki, Michal; Miller, Paul J.S.; Ribaud, Patricia; Schlamm, Haran T.; Solano, Carlos; Cook, Gordon (British journal of haematology, 2011)
Antifungal prophylaxis for allogeneic haematopoietic stem-cell transplant (alloHCT) recipients should prevent invasive mould and yeast infections (IFIs) and be well tolerated. This prospective, randomized, open-label, multicentre study compared the efficacy and safety of voriconazole (234 patients) versus itraconazole (255 patients) in alloHCT recipients. The primary composite endpoint, success of prophylaxis, incorporated ability to tolerate study drug for ≥100 d (with ≤14 d interruption) with survival to day 180 without proven/probable IFI. Success of prophylaxis was significantly higher with voriconazole than itraconazole (48·7% vs. 33·2%, P < 0·01); more voriconazole patients tolerated prophylaxis for 100 d (53·6% vs. 39·0%, P < 0·01; median total duration 96 vs. 68 d). The most common (>10%) treatment-related adverse events were vomiting (16·6%), nausea (15·8%) and diarrhoea (10·4%) for itraconazole, and hepatotoxicity/liver function abnormality (12·9%) for voriconazole. More itraconazole patients received other systemic antifungals (41·9% vs. 29·9%, P < 0·01). There was no difference in incidence of proven/probable IFI (1·3% vs. 2·1%) or survival to day 180 (81·9% vs. 80·9%) for voriconazole and itraconazole respectively. Voriconazole was superior to itraconazole as antifungal prophylaxis after alloHCT, based on differences in the primary composite endpoint. Voriconazole could be given for significantly longer durations, with less need for other systemic antifungals.
Gesehen am 10.08.2022